Statin Use With the ATP III Guidelines Compared to the 2013 ACC/AHA Guidelines in HIV Primary Care Patients. (February 2017) - Elsamadisi, Pansy; Cha, Agnes; Kim, Elise; Latif, Safia
Background: The 2013 Cholesterol Guidelines include a new atherosclerotic cardiovascular disease (ASCVD) risk calculator that determines the 10-year risk of coronary heart disease and/or stroke. The applicability of this calculator and its predecessor, the Framingham risk score (FRS) in Adult Treatment Panel (ATP) III, has been limited in patients with HIV. The objective of this study was to compare the risk scores of ASCVD and FRS in the initiation of statin therapy in patients with HIV. Methods: We conducted a retrospective chart review of patients with HIV on statin therapy from October 1, 2013, to April 1, 2014. Data collection included patient demographics, pertinent laboratory test results, and medication list. The primary end point evaluated the level of agreement between the guidelines. Results: Of 155 patients who met the inclusion criteria, 116 were treated similarly with both guidelines. This showed a moderate level of agreement ( P < .001). Forty-eight of 86 patients requiring statins were placed on the correct intensity statin using the 2013 guidelines. Regardless of which guideline, a majority of patients required statin therapy. Conclusion: A moderate agreement was found between both guidelines in terms of statin use when applied to an HIV patient population. Based on the 2013 guidelines and taking into account drug interactions with antiretrovirals, 44.2% of the patients were treated with an incorrect statin intensity.